Determination of Characteristic Peroids of Suppression of Thermal Decomposition Reaction of Forest Fuel Material by Specialized Software; MATEC Web of Conferences; Vol. 37 : Smart Grids 2015 - Gumerov V. M. Vladislav; Zhdanova A. O. Alena Olegovna; Osmolovskaya M. M. Maria; Strizhak P. A. Pavel Alexandrovich (2015, 2015)
Title screen